Emotional processes in learning situations (ISTE, Ltd. ; Wiley, 2022)
Emotional processes are increasingly studied in psychology, whether through their modes of expression or through their effect on cognitive processes. While the theorization of the link between emotional and cognitive processes has varied over the centuries, the impact of emotions on cognitive functions is now undeniable and is supported by experimental arguments. Psychological processes are currently considered necessary for, or influenced by, the emergence of emotions. Learning is at the heart of individual development and involves different cognitive processes; the study of the emotional processes at work in a learning situation must of course not be overlooked.